Determinants of the quality of internet investor relations – a study of companies listed on the JSE# - G. F. Nel; E. vdM. Smit; L. M. Brummer (South African Journal of Business Management, 2017)
Investor relations is the field of management that is concerned with the relationships between companies and investors, and as such involves a wide variety of information types, for example mandatory, voluntary, financial, non-financial, qualitative and quantitative. While South Africa has recently been ranked number one for the strength of its auditing and reporting standards for the seventh consecutive year (IRBA, 2016), investor relations as a wider and voluntary concept, is largely un-researched in South Africa. The purpose of the study was to establish the determinants of Internet investor relations (IIR).The quality of IIR was measured for a sample of 85 JSE-listed companies using a measurement instrument that consists of 346 attributes. From the literature, as discussed in the literature review, 15 company characteristics were identified that could explain IIR quality. Stepwise regression model-building was used to develop a regression model that best explains IIR quality.Company size, leverage, being audited by a big four audit company, JSE industry membership, free float and dual listing status were found statistically significant independent variables, explaining 68.76% of the variation in the dependent variable, IIR. Contributions to the body of knowledge, study limitations and the need for further research are discussed in the conclusion.
Keywords: 650